Coordination-resolved local bond contraction and electron binding-energy entrapment of Si atomic clusters and solid skins - Sun, Changqing (2014)
Consistency between x-ray photoelectron spectroscopy measurements and density-function theory calculations confirms our bond order-length-strength notation-incorporated tight-binding theory predictions on the quantum entrapment of Si solid skin and atomic clusters. It has been revealed that bond-order deficiency shortens and strengthens the Si-Si bond, which results in the local densification and quantum entrapment of the core and valence electrons. Unifying Si clusters and Si(001) and (111) skins, this mechanism has led to quantification of the 2p binding energy of 96.089 eV for an isolated Si atom, and their bulk shifts of 2.461 eV. Findings evidence the significance of atomic undercoordination that is of great importance to device performance.